Congresso EGraFia, Argentina 2018 (diségno, 2019)
After the previous successful Congress held in Argentina in 2012, the Faculty of Architecture and Urban Planning (National University of La Plata) was again chosen as the venue for the International Congress of Graphic Expression (VII International Congress of Engineering, Architecture and associated careers) jointly organised with EGraFia (XV National Congress of Engineering, Architecture and associated careers). The Congress was held on 4-5 October 2018